Pengaruh kualitas pelayan dan suasana terhadap loyalitas pelanggan melalui kepuasan pelanggan di The Oakroom Whiskybar Jakarta - Rossiana Kiki Setiowati; Yosafat Puji Hastoko (LPPM Universitas Asa Indonesia, 2022)
This study aims to determine the effect of service quality and atmosphere on customer loyalty through customer satisfaction at The Oakroom Whiskeybar Jakarta. Customers of The Oakroom are respondents in this study. The sampling technique used purposive sampling as many as 100 customers as respondents. The data analysis method in this study used quantitative descriptive. This study uses the Structural Equation Model (SEM). By using the SmartPLS 3.0 application as the data processing. The results of hypothesis testing indicate that service quality has a positive and significant effect on customer loyalty. Service quality has a positive and significant effect on customer satisfaction. The atmosphere has a positive and significant impact on customer loyalty. Atmosphere has a positive and significant effect on customer satisfaction. Meanwhile, customer satisfaction does not have a positive and significant effect on customer satisfaction. Service quality has no positive and significant effect on customer loyalty through customer satisfaction. The atmosphere has no positive and significant effect on customer loyalty through customer satisfaction. Keywords : Service Quality, Store Atmosphere, Customer Loyality, Customer Satisfaction